NaA type zeolite molecular sieve as well as preparation method and application thereof
By using fly ash as raw material to prepare NaA zeolite molecular sieve, the problem of poor adsorption of adsorption method selection and prone to secondary pollution in the prior art is solved, and efficient adsorption of impurities in aqueous caprolactam solution is achieved, and production costs and energy consumption are reduced.
Patent Information
- Application Number
- CN202510055521.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art In the refining process of caprolactam, the adsorption method has the problem of poor selective adsorption properties and is easily caused by temperature influence, and it is difficult to effectively remove impurities in the aqueous caprolactam solution.
NaA type zeolite molecular sieve is prepared by using fly ash as raw material, and impurities in the aqueous caprolactam solution are adsorbed with its good adsorption and selective exchangeability. The preparation method includes pretreatment of fly ash, preparing a precursor and obtaining NaA-type zeolite molecular sieve by hydrothermal crystallization.
The conductivity of the aqueous caprolactam solution is significantly reduced by about 82.3% and the extinction value is about 58.9%, and the zeolite molecular sieve is easy to regenerate, has excellent structural stability, and is suitable for large-scale production.
Smart Images

Figure BDA0005241304050000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of zeolite molecular sieve adsorption, and in particular relates to a NaA zeolite molecular sieve and a preparation method and application thereof. Background Art
[0002] Caprolactam is an important chemical raw material, mainly used to produce nylon-6 fiber and engineering plastics. Nylon-6 fiber can be used for civil textiles, industrial yarns, etc.; nylon-6 resin can be used as components and assemblies of automobiles, electronic appliances, industrial machinery and daily necessities. The production process of caprolactam is long and complex, and a large number of raw materials are used, resulting in more than 30 types of impurities in the synthesized crude caprolactam. Although the content of these impurities is low, mostly in the microgram level or even lower, they seriously affect the quality of the finished caprolactam.
[0003] No matter benzene extraction, water back extraction, alkali washing, ion exchange, hydrogenation are all for removing various impurities in crude caprolactam, but often the removal effect is not ideal, the finished product conductivity is high, the extinction value is easily exceeded, the cost is high, and the economic benefit is poor. At present, the process of caprolactam refining is mainly reflected in new equipment and new technology. There is a prior art that provides a method for decompression distillation to remove light crystals to obtain high-purity caprolactam, and there is a prior art that provides a novel caprolactam hydrogenation equipment, so that hydrogen and caprolactam solution are uniformly mixed to improve the purification effect, but the cost is high, and the refining and impurity removal effect is poor. In the existing technology, the adsorption method has the advantages of high efficiency and stability in treatment performance and low investment, and is therefore widely used in the field of purification and impurity removal. There is also the prior art that uses activated carbon as an adsorbent, and the impurities in the caprolactam aqueous solution are processed by the method of centrifugation and adsorption, but the activated carbon has poor selective adsorption, is affected by temperature, and is prone to secondary pollution and other problems. Zeolite molecular sieve is a porous structure of hydrated aluminosilicate compounds, its internal pore size distribution is uniform, with good adsorption and selective exchange, its special aluminosilicate lattice pores determine its strong adsorption, so it is currently widely used as an excellent adsorbent. Fly ash is the fine ash collected from the flue gas after coal combustion. It is currently one of the largest industrial solid wastes and the largest single solid pollution source in my country. The preparation of zeolite molecular sieves with cheap fly ash to adsorb impurities in caprolactam aqueous solution is undoubtedly in line with the country's "dual carbon" policy. Summary of the invention
[0004] In view of this, the main purpose of the present invention is to provide a NaA zeolite molecular sieve and a preparation method and application thereof, by using fly ash as a raw material to prepare a NaA zeolite molecular sieve with good adsorption performance, easy regeneration and excellent structural stability.
[0005] In order to achieve the above object, the present invention provides a method for preparing NaA zeolite molecular sieve, comprising the following steps:
[0006] S1 pretreatment: calcining the dried and ground fly ash, cooling it to room temperature and grinding the fly ash to obtain pretreated fly ash powder;
[0007] Preparation of S2 precursor: The pretreated fly ash and HCl solution are stirred at room temperature, cooled, filtered, washed until the pH is neutral, dried and ground to 200 mesh, NaOH and NaAlO2 are added and mixed, and then calcined to obtain a green precursor powder;
[0008] Preparation of S3 adsorbent: The green precursor powder and water are mixed in proportion, stirred and ultrasonically dispersed, the mixture is hydrothermally crystallized, and the NaA type zeolite molecular sieve is obtained after cooling, filtering and washing.
[0009] Furthermore, in step S1, the basic chemical composition of the fly ash is as follows, calculated by mass percentage: SiO2 54.6%, CaO 3.73%, Al2O3 30.02%, Fe2O3 4.83%, MgO 0.64%, Na2O 1.44%, K2O 0.72%, and TiO2 0.21%.
[0010] Furthermore, in step S1, the fly ash particle size is 100-400 mesh.
[0011] Furthermore, in step S1, the calcination temperature is 700-1000°C.
[0012] Furthermore, in step S1, the calcination time is 1 to 3 hours.
[0013] Furthermore, in step S2, the solid-liquid ratio of the fly ash to the HCl solution is 1:3-6; the mass ratio of the fly ash, NaOH and NaAlO2 is 1:(1-1.6):(0.1-0.3).
[0014] Furthermore, in step S2, the concentration of the HCl solution is 5 to 10 mol / L, the solid-liquid ratio is 1:2 to 10, and the stirring time is 1 to 5 h.
[0015] Furthermore, in step S2, the calcination temperature is 500-800° C., and the calcination time is 1-8 hours.
[0016] Furthermore, in step S3, the stirring time is 1 to 2 hours, the ultrasonic dispersion time is 5 to 10 minutes, and the solid-liquid ratio of the precursor to water is 1:5 to 10.
[0017] Furthermore, in step S3, the hydrothermal crystallization temperature is 70-100° C., and the hydrothermal crystallization time is 6-18 hours.
[0018] Furthermore, in step S3, the pH value of the NaA type zeolite molecular sieve is 4-10.
[0019] In order to achieve the above-mentioned purpose, the present invention also provides a NaA type zeolite molecular sieve, which has a specific surface area of 78.44m 2 / g-141.24m 2 / g, the NaA type zeolite molecular sieve is prepared by any of the methods described above.
[0020] In order to achieve the above-mentioned purpose, the present invention also provides a use of a NaA type zeolite molecular sieve for adsorbing impurities in a caprolactam aqueous solution.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses fly ash as raw material to absorb some impurities in the caprolactam aqueous solution. The preparation process is simple and the production efficiency is high. It can not only absorb fly ash solid waste, but also reduce production costs and energy consumption, which is conducive to large-scale production.
[0023] 2. The present invention can significantly adsorb NH4 in caprolactam aqueous solution + , reducing the conductivity of caprolactam aqueous solution by about 82.3% and the extinction value by about 58.9%;
[0024] 3. The desorption of the present invention is simple and can be reused. The regeneration method is as follows: soaking and washing in 0.4 mol / L sodium chloride solution for 24 hours, controlling the regeneration pH to be neutral, and the regeneration temperature to be room temperature. DETAILED DESCRIPTION
[0025] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of the specific implementation, characteristics and performance of the NaA type zeolite molecular sieve and its preparation method and its application in adsorbing caprolactam impurities according to the present invention in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, the specific features, structures or characteristics in one or more embodiments can be combined in any suitable form.
[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0027] The following materials or reagents, unless otherwise specified, were purchased from the market.
[0028] An embodiment of the present invention provides a method for preparing a NaA zeolite molecular sieve, comprising the following steps:
[0029] S1 pretreatment: calcining the dried and ground fly ash in a muffle furnace to remove unburned carbon, cooling to room temperature and grinding the fly ash to obtain pretreated fly ash powder;
[0030] Preparation of S2 precursor: The pretreated fly ash and HCl solution are stirred at room temperature in a conical flask at a solid-liquid ratio of 1:3-6, cooled, filtered, washed until the pH is neutral, dried and ground to 100-400 mesh. In order to improve the dissolution of the silicon-aluminum layer in the fly ash and avoid the generation of different crystalline phases, the fly ash, NaOH, and NaAlO2 are mixed in a mass ratio of 1: (1-1.6): (0.1-0.3) and calcined in a muffle furnace to obtain a green precursor powder; when the mass ratio of the fly ash, NaOH, and NaAlO2 is less than the lower limit, the silicon-aluminum layer in the fly ash is not easy to dissolve; when the mass ratio of the fly ash, NaOH, and NaAlO2 is greater than the upper limit, calcination is prone to produce impurities. If it is less than 100 mesh, the particle size is too small, resulting in strong particle adhesion, easy agglomeration, and difficult to filter; if it is greater than 400 mesh, it will lead to incomplete reaction.
[0031] Preparation of S3 adsorbent: The green precursor powder and water are mixed in proportion, stirred for 1 to 2 hours to make the mixture uniform, and ultrasonically dispersed for 5 to 10 minutes to make the precursor more dispersed, and the obtained mixture is placed in a vacuum drying oven for hydrothermal crystallization, cooled to room temperature, filtered, washed with distilled water until neutral, and dried to obtain NaA type zeolite molecular sieve. The hydrothermal crystallization temperature is 70 to 100°C, and the hydrothermal crystallization time is 6 to 18 hours.
[0032] In some embodiments, optionally, in step S1, the basic chemical composition of the fly ash, calculated by mass percentage, is as follows: SiO2 54.6%, CaO 3.73%, Al2O3 30.02%, Fe2O3 4.83%, MgO 0.64%, Na2O 1.44%, K2O 0.72%, TiO2 0.21%, and the specific components are shown in Table 1 below, but are not limited to the above-listed values, and other unlisted grades within the range are also applicable.
[0033] Table 1 Chemical element composition of fly ash (wt / %)
[0034] Fly ash <![CDATA[SiO2]]> CaO <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> MgO <![CDATA[Na2O]]> <![CDATA[K2O]]> <![CDATA[TiO2]]> grade 54.6 3.73 30.02 4.83 0.64 1.44 0.72 0.21
[0035] In some embodiments, optionally, in order to avoid the particle size being too small (such as less than 100 mesh) resulting in strong particle adhesion, easy agglomeration, and difficulty in filtering; or the particle size being too large (such as greater than 400 mesh) resulting in incomplete reaction. Therefore, in step S1, the particle size of the ground fly ash is set to 100-400 mesh, such as 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, etc., but is not limited to the above-listed values, and other unlisted mesh numbers within the range are also applicable. To ensure a more complete calcination reaction, 200 mesh is preferred.
[0036] In some embodiments, optionally, in step S1, the calcination temperature is 700-1000°C, the purpose of which is to activate the fly ash. If the temperature is too low, the activation reaction is incomplete, and if the temperature is too high, it is easy to agglomerate and cause the reaction phase to dissolve. However, it is not limited to this range, and values not listed in other ranges are also applicable. Considering the activation performance, the calcination temperature is preferably 900°C.
[0037] In some embodiments, optionally, in step S1, the calcination time is 1 to 3 hours, and in order to ensure the complete activation reaction and avoid agglomeration effect, 200 mesh is preferred.
[0038] In some embodiments, optionally, in step S2, to ensure the sufficiency of the reaction, the concentration of the HCl solution used is 5 to 10 mol / L, the solid-liquid ratio is 1:2 to 10, and the stirring time is 1 to 5 h.
[0039] In some embodiments, optionally, in step S2, the mixture is calcined in a muffle furnace at a temperature of 500 to 800° C. and a calcination time of 1 to 8 hours.
[0040] As a further embodiment, in order to ensure alkali resistance and experimental effect, the crucible calcined in step S2 of the present invention is a nickel crucible. The nickel crucible has good alkali resistance and corrosion resistance.
[0041] In some embodiments, optionally, in step S3, in order to ensure that the precursor and water are mixed more fully, the solid-liquid ratio is 1:5-10.
[0042] In some embodiments, optionally, in step S3, if the temperature is too low and the time is too short, the molecular sieve crystallization is incomplete, and if the temperature is too high and the time is too long, the molecular sieve crystallization effect is destroyed. Therefore, the vacuum drying crystallization temperature is controlled to be 70-100°C, and the crystallization time is 6-18h.
[0043] In some embodiments, optionally, in step S3, the pH value of the NaA zeolite molecular sieve is controlled to be 4-10. A pH value less than 4 or a pH value greater than 10 will destroy the structure of the molecular sieve. The pH value is preferably 7.
[0044] The embodiment of the present invention further provides a NaA type zeolite molecular sieve, which uses fly ash as raw material and has a chemical formula of Na x ·(SiO4) y ·(AlO4) z ·(H2O) n It is a three-dimensional grid structure with silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron as the skeleton, with large specific surface area and porosity. Its specific surface area is 78.44m 2 / g-141.24m 2 / g, good adsorption performance, can effectively adsorb NH4 in caprolactam aqueous solution + Impurities, the NaA type zeolite molecular sieves of Examples 1-4 reduce the conductivity by about 17%-93.9% compared with that of Comparative Example 2; the NaA type zeolite molecular sieve is prepared by any of the methods described above.
[0045] An embodiment of the present invention further provides a use of a NaA type zeolite molecular sieve for adsorbing impurities in a caprolactam aqueous solution.
[0046] The method provided by the present invention is further illustrated by the following examples, but is not limited to the following examples.
[0047] Example 1
[0048] Take 50g of fly ash that has passed through a 200-mesh sieve and calcine it in a muffle furnace for 2h, control the calcination temperature to 900℃ to remove unburned carbon, then cool the fly ash to room temperature, grind it, and pass it through a 200-mesh sieve. Take 100g of pretreated fly ash, add 500g of 8mol / L hydrochloric acid solution, stir it with a magnetic stirrer at room temperature for 2h, cool, filter, wash it with deionized water to neutrality, dry it in a 60℃ blast drying oven for 2h, grind it and pass it through a 200-mesh sieve. Take 50g of sample, add 3g of NaOH powder and 3g of NaAlO2 powder, mix well, and calcine it in a muffle furnace for 3h, control the temperature to 1000℃, grind it after cooling, and pass it through a 200-mesh sieve to obtain a molecular sieve precursor.
[0049] Take 30g of molecular sieve precursor, add 300mL of deionized water, stir for 2h, disperse in ultrasonic disperser for 10min, place the mixture in a vacuum drying oven at 80℃ for hydrothermal crystallization for 12h, cool to room temperature, filter, wash to pH 7, and dry to obtain zeolite molecular sieve adsorbent①. The surface area of the adsorbent is 108.49m 2 / g.
[0050] Take 1 g of the zeolite molecular sieve adsorbent ① obtained above, 100 mL of caprolactam aqueous solution after ion exchange (the conductivity of the supernatant is 1.47 μs / cm, and the extinction value is 0.18), mix at 45°C and stir thoroughly for 12 hours, take out and centrifuge (speed 2500 r / min, time 10 min) and then test the supernatant. The specific results are shown in Table 2 below.
[0051] Example 2
[0052] Take 50g of fly ash that has passed through a 200-mesh sieve and calcine it in a muffle furnace for 2h, control the calcination temperature to 900℃ to remove the incompletely burned carbon, then cool the fly ash to room temperature, grind it, and pass it through a 200-mesh sieve. Take 100g of pretreated fly ash, add 500g of 8mol / L hydrochloric acid solution, stir it with a magnetic stirrer at room temperature for 2h, cool, filter, wash it with deionized water to neutrality, dry it in a 60℃ blast drying oven for 2h, grind it and pass it through a 200-mesh sieve. Take 50g of sample, add 3g of NaOH powder and 3g of NaAlO2 powder, mix well, and calcine it in a muffle furnace for 3h, control the temperature to 700℃, grind it after cooling, and pass it through a 200-mesh sieve to obtain a molecular sieve precursor.
[0053] Take 30g of the precursor, add 300mL of deionized water, stir for 2h, disperse in an ultrasonic disperser for 10min, place the mixture in a 100℃ vacuum drying oven for hydrothermal crystallization for 12h, cool to room temperature, filter, wash to pH 7, and dry to obtain zeolite molecular sieve adsorbent ②. The surface area of the adsorbent is 97.61m 2 / g.
[0054] Take 1 g of the zeolite molecular sieve adsorbent ② obtained above, 100 mL of the caprolactam aqueous solution after ion exchange (the conductivity of the supernatant is 1.47 μs / cm, and the extinction value is 0.18), mix them at 45°C and stir them thoroughly for 12 hours, take out the supernatant and test it after centrifugation. The specific results are shown in Table 2 below.
[0055] Example 3
[0056] Take 50g of fly ash that has passed through a 200-mesh sieve and calcine it in a muffle furnace for 2h, control the calcination temperature to 900℃ to remove the incompletely burned carbon, then cool the fly ash to room temperature, grind it, and pass it through a 200-mesh sieve. Take 100g of pretreated fly ash, add 500g of 8mol / L hydrochloric acid solution, stir it with a magnetic stirrer at room temperature for 2h, cool, filter, wash it with deionized water to neutrality, dry it in a 60℃ blast drying oven for 2h, grind it and pass it through a 200-mesh sieve. Take 50g of sample, add 3g of NaOH powder and 3g of NaAlO2 powder, mix well, and calcine it in a muffle furnace for 3h, control the temperature to 700℃, grind it after cooling, and pass it through a 200-mesh sieve to obtain a molecular sieve precursor.
[0057] Take 30g of the precursor, add 300mL of deionized water, stir for 2h, disperse in an ultrasonic disperser for 10min, place the mixture in a vacuum drying oven at 80℃ for hydrothermal crystallization for 12h, cool to room temperature, filter, wash to pH 5, and dry to obtain zeolite molecular sieve adsorbent ③. The surface area of the adsorbent is 78.44m 2 / g.
[0058] Take 1 g of the zeolite molecular sieve adsorbent ③ obtained above, 100 mL of the caprolactam aqueous solution after ion exchange (the conductivity of the supernatant is 1.47 μs / cm, and the extinction value is 0.18), mix them at 45°C and stir them thoroughly for 12 hours, take out the supernatant and test it after centrifugation. The specific results are shown in Table 2 below.
[0059] Example 4
[0060] Take 50g of fly ash that has passed through a 200-mesh sieve and calcine it in a muffle furnace for 2h, control the calcination temperature to 900℃ to remove the incompletely burned carbon, then cool the fly ash to room temperature, grind it, and pass it through a 200-mesh sieve. Take 100g of pretreated fly ash, add 500g of 8mol / L hydrochloric acid solution, stir it with a magnetic stirrer at room temperature for 2h, cool, filter, wash it with deionized water to neutrality, dry it in a 60℃ blast drying oven for 2h, grind it and pass it through a 200-mesh sieve. Take 50g of sample, add 3g of NaOH powder and 3g of NaAlO2 powder, mix well, and calcine it in a muffle furnace for 3h, control the temperature to 700℃, grind it after cooling, and pass it through a 200-mesh sieve to obtain a molecular sieve precursor.
[0061] Take 30g of the precursor, add 300mL of deionized water, stir for 2h, disperse in an ultrasonic disperser for 10min, place the mixture in a vacuum drying oven at 80℃ for hydrothermal crystallization for 12h, cool to room temperature, filter, wash to pH 7, and dry to obtain a zeolite molecular sieve adsorbent④, which has a surface area of 141.24m 2 / g.
[0062] Take 1 g of the zeolite molecular sieve adsorbent ④ obtained above, 100 mL of caprolactam aqueous solution after ion exchange (the conductivity of the supernatant is 1.47 μs / cm, and the extinction value is 0.18), mix at 45°C and stir thoroughly for 12 hours, take out the supernatant and test it after centrifugation. The specific results are shown in Table 2 below.
[0063] Comparative Example 1
[0064] Take 1g of fly ash after drying and grinding and pass through a 200-mesh sieve (its surface area is 14.69m 2 / g), 100 mL of caprolactam aqueous solution after ion exchange was mixed and kept warm at 45°C and stirred for 12 h. The supernatant was taken out and centrifuged to test the supernatant. The specific results are shown in Table 2 below.
[0065] Comparative Example 2
[0066] The caprolactam aqueous solution after ion exchange without any treatment was taken, and the conductivity of the supernatant was 1.47 μs / cm and the extinction value was 0.18. The test and comparison were carried out. The specific results are shown in Table 2 below.
[0067] Table 2 Test results of Examples 1-4 and Comparative Examples 1-2
[0068]
[0069]
[0070] It can be seen from the data in Table 2 that, when other conditions of the above embodiment remain unchanged, the calcination temperature is controlled to be 1000°C, the crystallization temperature is controlled to be 80°C, and the pH value after washing is controlled to be 7. The adsorption performance of the finally prepared NaA type zeolite molecular sieve adsorbent is optimal. At this time, the conductivity of the hexyl water supernatant is 0.26μs / cm, and the extinction value is 0.074.
[0071] The above embodiments are only used for the technical solutions of the present invention, but not to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it should be understood by those skilled in the art that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing NaA zeolite molecular sieve, characterized in that: The following steps are involved: S1 pretreatment: calcining the dried and ground fly ash, cooling it to room temperature and grinding the fly ash to obtain pretreated fly ash powder; Preparation of S2 precursor: The pretreated fly ash and HCl solution are stirred at room temperature, cooled, filtered, washed until the pH is neutral, dried and ground to 200 mesh, NaOH and NaAlO2 are added and mixed, and then calcined to obtain a green precursor powder; Preparation of S3 adsorbent: The green precursor powder and water are mixed in proportion, stirred and ultrasonically dispersed, the mixture is hydrothermally crystallized, and the NaA type zeolite molecular sieve is obtained after cooling, filtering and washing.
2. The method for preparing NaA zeolite molecular sieve according to claim 1, characterized in that: In step S1, the basic chemical composition of the fly ash is as follows, by mass percentage: SiO2 54.6%, CaO 3.73%, Al2O3 30.02%, Fe2O3 4.83%, MgO 0.64%, Na2O 1.44%, K2O 0.72%, and TiO2 0.21%.
3. The method for preparing NaA zeolite molecular sieve according to claim 1, characterized in that: In step S1, the fly ash particle size is 100-400 mesh.
4. The method for preparing NaA zeolite molecular sieve according to claim 1, characterized in that: In step S1, the calcination temperature is 700-1000° C.; the calcination time is 1-3 hours.
5. The method for preparing NaA zeolite molecular sieve according to claim 1, characterized in that: In step S2, the fly ash and HCl solution are in a solid-liquid ratio of 1:3-6; the mass ratio of the fly ash, NaOH and NaAlO2 is 1:(1-1.6):(0.1-0.3); the concentration of the HCl solution is 5-10 mol / L, the solid-liquid ratio is 1:2-10, and the stirring time is 1-5h.
6. The method for preparing NaA zeolite molecular sieve according to claim 1, characterized in that: In step S2, the calcination temperature is 500-800°C, and the calcination time is 1-8 hours.
7. The method for preparing NaA zeolite molecular sieve according to claim 1, characterized in that: In step S3, the stirring time is 1 to 2 hours, the ultrasonic dispersion time is 5 to 10 minutes, and the solid-liquid ratio of the precursor to water is 1:5 to 10.
8. The method for preparing NaA zeolite molecular sieve according to claim 1, characterized in that: In step S3, the hydrothermal crystallization temperature is 70-100° C., the hydrothermal crystallization time is 6-18 hours; and the pH value of the NaA type zeolite molecular sieve is 4-10.
9. A NaA type zeolite molecular sieve, characterized in that: Its specific surface area is 78.44m 2 / g-141.24m 2 / g, the NaA type zeolite molecular sieve is prepared by the method according to any one of claims 1-8.
10. Use of the NaA type zeolite molecular sieve according to claim 9 for adsorbing impurities in a caprolactam aqueous solution.